The Relationship of Knowledge, Attitudes, and Practices on the Use of Personal Protective Equipment with the Incident of Work Accidents - Vidi Posdo A. Simarmata; Wendy Hendrika (GLOBAL HEALTH SCIENCE GROUP, 2025)
The World Health Organization (WHO) reports that more than 2 million health workers are exposed to injuries from sharp objects, including injuries from needle sticks, every year. Health workers experience more than 2 million injuries from sharp objects at work every year. This injury causes approximately 16,000 cases of hepatitis C virus (HCV) infection, 66,000 cases of hepatitis B virus (HBV), and 1,000 cases of Human Immunodeficiency Virus (HIV) infection. Objective: determine the relationship between knowledge, attitudes, and practices in the use of personal protective equipment with work accident rates among Merdeka Health Center health workers in 2025. Method: This research uses an analytical observational research type with the research design used is a cross-sectional study with a sampling technique using the Total Sampling technique. 31 respondents had data according to the inclusion criteria. The data in this study are primary data because they were collected by the researcher himself and obtained directly from the respondents. Information was collected through a digital questionnaire sheet that would be given to the respondents. Before filling out the questionnaire. Data analysis was conducted using univariate, bivariate, and multivariate methods by the spss application.Results: There is a significant relationship between knowledge and the incidence of work accidents (P value 0.015) with an Odds Ratio value of 0.111 and a Confidence Interval of 0.019-0.645. There is a significant relationship between attitude and the incidence of work accidents (P value 0.022) with an Odds Ratio analysis of 0.105 and a Confidence Interval of 0.016-0.713. There is a significant relationship between the practice of using personal protective equipment and the incidence of work accidents (P value 0.004) with an Odds Ratio analysis of 0.071 and a Confidence Interval of 0.012-0.442.Conclusions: There is a significant relationship between knowledge, attitudes, and practices of using personal protective equipment and work accidents among health workers at the Merdeka Health Center, Bogor City in 2025.